Adoption of agronomic practices and their impact on crop yield and income: an analysis for black gram and green gram in India - Varma, P.; Manda, J. (Wiley, 2025)
Black gram and green gram are important pulse crops in India, but their production has faced fluctuations and stagnancy in yields over the last few decades. The Government of India has implemented several measures to enhance crop yield, including recommending and promoting the adoption of crop-specific agronomic practices. However, there is limited empirical evidence on the determinants of the adoption of these practices and their impact on yield and income. In this context, this study analyses the determinants of the adoption of climate and plant management practices among black gram and green gram farmers and their impact on yield, crop revenue and net income across four major crop-producing Indian states using a multinomial endogenous treatment effects model. Our analysis shows that information, contact with government extension services and access to off-farm activities are crucial in adopting climate and plant management practices. The results strengthen the view that the adoption of knowledge-intensive practices happens via formal information sources and plot-level demonstrations. In addition, the results indicate that farmers who experience frequent crop loss exhibit an aversion towards adopting climate and plant management practices. While adopting these practices had a positive impact on crop yield and crop revenue, the impact on net income was observed only in the case of climate management.